MEASUREMENT OF ISLAMIC FINANCIAL LITERACY IN ISLAMIC FAMILY FINANCIAL MANAGEMENT : LITERATURE REVIEW - Nelsi Arisandy; Afrizal Afrizal; Wirmie Eka Putra; Rico Wijaya Z (Faculty of Economic and Social Science, Universitas Islam Negeri Sultan Syarif Kasim, 2024)
Islamic Financial Literacy is an insight that a person has about Islamic financial products and services and is a type of sharia-based finance in Islamic life and law. This knowledge will ultimately have implications for a person's attitude in making economic decisions in accordance with Islamic values. This study discusses the indicators used in measuring Islamic financial literacy in Islamic family financial management using a structured systematic literature review methodology that uses 40 scientific articles indexed by Scopus and accredited by SINTA. The background of this study is because the statistics of divorces caused by economic problems show astonishing numbers. The measurement of Islamic financial literacy is also a combination of several qualitative and quantitative studies. The results of the study show that the indicators used in measuring Islamic financial literacy are zakat, deposits and loans in Islam, sharia insurance, sharia investment and household consumption. The purpose of this study is to provide an understanding of the importance of Islamic financial literacy related to the financial management of Islamic households, so that the goals of Sakinah Mawaddah Warrahmah Islamic households can be achieved.